Modified Pulsatilla decoction ameliorates ulcerative colitis by affecting gut microbiota and metabolite profiles - Fu, Zhixin; Xie, Xiangyue; Wang, Yulei; Wang, Zhen; Wu, Anran; Ye, Shaotang; Liu, Yongbo (Frontiers in Microbiology, 2025)
To investigate the therapeutic effects of a specific modified Pulsatilla decoction (MPD) on ulcerative colitis (UC) in mice, 32 male Balb/c mice were randomly assigned to four groups: Control, Model, High-dose (H-dose), and Low-dose (L-dose), with eight mice per group. All groups except the Control group were administered 3% dextran sulfate sodium (DSS) in their drinking water for 7 days to induce acute UC. The H-dose group and L-dose group mice were gavaged, respectively, with different concentrations of MPD, while the Control group and Model group received the same amount of steriled water by gavage. Clinical symptoms of the mice were observed and recorded throughout the study. Subsequently, pathological sections of the colon tissues were prepared, and 16S rRNA high-throughput sequencing and metabolomics analysis were conducted on the intestinal contents. The results indicated that MPD improved the structure and morphology of colon tissue, significantly reducing inflammatory damage in DSS-treated mice. Furthermore, MPD alleviated DSS-induced intestinal injury by enhancing the abundance of beneficial intestinal probiotics, such as Actinobacteriota and Oscillospirates. Metabolomic analysis revealed significant changes in the MPD group compared to the Model group, with 53 metabolites upregulated and 22 downregulated. Key upregulated metabolites included Esculetin, Glutarate semialdehyde, and Licoricone, while downregulated metabolites included Ectoine and Trans-Piceid. KEGG enrichment analysis indicated that MPD primarily targets pathways such as linoleic acid metabolism, VEGF signaling, and glutamatergic synapse, highlighting its potential regulatory effects. In conclusion, we revealed that this MPD has the potential to alleviate DSS-induced colitis by reducing inflammation, regulating intestinal microbiota and intestinal metabolism.